Personal Ties in the Writing of a Doctoral Dissertation - Laura Colombo (Universidad Autónoma de Baja California, 2014)
The problem of low graduation rates at the graduate level has been linked to the challenges of dissertation work. Given that this is a process of "disciplinary enculturation", where graduate students acquire the ways of being and doing of each discipline, the social relations of doctoral candidates should be analyzed. Several studies have explored the support provided by social ties within academia but have, nevertheless, ignored other spheres. This qualitative study, based on in-depth interviews, explores the personal-sphere social relations in the dissertation writing process from the point of view of doctoral candidates and recent graduates in the fields of Education and Linguistics. Results indicate that the emotional, financial, economic, and academic support offered by these social ties is a necessary, although not in itself, sufficient condition. Some strategies for increasing institutional support to facilitate the process of writing a dissertation are offered.